The Effectiveness of The Problem Based Learning Model Assisted by Scientific Articles to Improve Student Learning Outcomes in Excretory System Material - Aeni, Riska Nuril; Iswari, Retno Sri (FMIPA UNNES, 2020)
The 2013 curriculum is related to four models that are recommended to be implemented, one of them is the Problem Based Learning (PBL) model. The innovation of the PBL model is shown by the existence of scientific articles as students' media in solving problems. Excretory system material is a material related to students' daily activities regarding the process of excreting substances from the body and student's environment. The purpose of this study is to analyze the effectiveness of the PBL model assisted by scientific articles. This study is a Quasi-Experimental Research with Non-equivalent Control Group Design and the sampling technique used was simple random sampling. The research subjects were XI MIPA 1 (Control Class) and XI MIPA 2 (Experiment Class). The data obtained were in the form of cognitive scores (pre test and post test), skill scores, attitude scores, student responses, and teacher responses. The average score of the post test score for the experimental class was 68.75, and the posttest score for the control class was 62.50. Student psychomotor learning outcomes are categorized into good and very good criteria. Likewise, affective learning outcomes show all students have an attitude of discipline, honesty, responsibility, and cooperation. The results showed (1) there were differences in learning outcomes beetween classes using the PBL model assisted by scientific articles and the class using discovery model and student scores in the experimental class were higher, (2) the increase in learning outcomes of medium and high criteria class using the PBL PBL model assisted by scientific articles is better than the class using discovery model. Thus, the PBL model assisted by scientific articles is effective in improving student learning outcomes in the excretory system material